2010
DOI: 10.1073/pnas.1000318107
|View full text |Cite
|
Sign up to set email alerts
|

Activin A, a product of fetal Leydig cells, is a unique paracrine regulator of Sertoli cell proliferation and fetal testis cord expansion

Abstract: Formation of tubular structures relies upon complex interactions between adjacent epithelium and mesenchyme. In the embryonic testes, dramatic compartmentalization leads to the formation of testis cords (epithelium) and the surrounding interstitium (mesenchyme). Sertoli cells, the epithelial cell type within testis cords, produce signaling molecules to orchestrate testis cord formation. The interstitial fetal Leydig cells, however, are thought only to masculinize the embryo and are not known to be involved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
113
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(124 citation statements)
references
References 47 publications
8
113
0
3
Order By: Relevance
“…Ectopic activation of Bmp2 and follistatin might be one cause of dysgenesis of the testicular cords. Either conditional deletion of Smad4 in Sertoli cells or specific KO of the gene for activin βA in fetal Leydig cells decreased Sertoli cell proliferation and caused abnormal testicular histology (Archambeault and Yao, 2010). We therefore suggest that nodal/activin-A acts on Sertoli cells to promote cell proliferation and suppress female differentiation.…”
Section: Research Articlementioning
confidence: 94%
See 2 more Smart Citations
“…Ectopic activation of Bmp2 and follistatin might be one cause of dysgenesis of the testicular cords. Either conditional deletion of Smad4 in Sertoli cells or specific KO of the gene for activin βA in fetal Leydig cells decreased Sertoli cell proliferation and caused abnormal testicular histology (Archambeault and Yao, 2010). We therefore suggest that nodal/activin-A acts on Sertoli cells to promote cell proliferation and suppress female differentiation.…”
Section: Research Articlementioning
confidence: 94%
“…However, ectopic meiosis and the loss of NANOS2 expression in some germ cells indicates the existence of a SMAD4-dependent pathway, by which nodal/activin signaling directly regulates male germ cell fate. Moreover, if other somatic factors are triggered by nodal/activin-A that affect male germ cell fate, exclusive interruption of nodal/activin signals in somatic cells should give rise to defects in germ cells, whereas conditional deletion of Smad4 in Sertoli cells was associated with grossly normal spermatogenesis (Archambeault and Yao, 2010), implying the absence or limited function of these factors. Hence, our study presents the first evidence that nodal/activin signals act directly on germ cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La diferenciación de las célu-las intersticiales (de Leydig) es regulada por el morfógeno Desert Hedgehog (DHH), secretado por las células sustentaculares (Pierucci-Alves et al, 2001), aunque también están involucrados el factor de crecimiento derivado de plaquetas (PDGFA) y el gen Homeobox Arx (Griswold & Behringer). A su vez, las células intersticiales fetales poseen receptores Patched1 (PTCH1) para DHH y PDGFRA para PDGFA, y responden produciendo activina A, el cual actúa como un regulador paracrino de la proliferación de los sustentocitos y de la expansión del cordón testicular (Archambeault & Yao, 2010).…”
Section: Desarrollo De Las Células Intersticialesunclassified
“…In a recent article, Archambeault and Yao (1) reported that genetic disruption of activin A resulted in a failure of fetal testiscord elongation and expansion because of decreased Sertoli cell proliferation. They uncovered a role of fetal Leydig cells during testis-cord morphogenesis through activin A signaling pathway.…”
mentioning
confidence: 99%